45.4k views
1 vote
Number 13 please thanks

Number 13 please thanks-example-1

1 Answer

2 votes

Answer:

(3, - 9)

Explanation:

Differentiate using the power rule

y = a
x^(n) , then


(dy)/(dx) = na
x^(n-1)

Given

y = x² - 6x


(dy)/(dx) = 2x - 6

Equate to zero since the measure of gradient is
(dy)/(dx) , that is

2x - 6 = 0 ( add 6 to both sides )

2x = 6 ( divide both sides by 2 )

x = 3

Substitute x = 3 into y for corresponding value of y

y = 3² - 6(3) = 9 - 18 = - 9, thus

(3, - 9 ) are the coordinates of the point where the gradient is zero

User Vince VD
by
4.8k points